European Autonomy in Space - Al-Ekabi, Cenan (Springer, 2015)
The volume provides analyses and evaluations of the continuing importance of Europe’s autonomy in its access to space as a key driver in the development of European space capabilities. From a detailed historical analysis of some of the pitfalls of dependence in the space industry, experts analyse the full range of current European space capabilities and identify areas where autonomy is both possible and required, even in a situation of severe budgetary constraints.